Factors Influencing the Students’ Interest in Continuing Their Education to University - Sakdiah, Halimatus (Jurnal Pendidikan Progresif, 2018)
Objectives: The purpose of this study is to find out how much interest high school students continue their education to college and what factors influence it. Methods: This study uses a quantitative method that uses a questionnaire that is valid and reliable as an instrument. Findings: The results of this study indicate that the interest of high school students in Sungai Penuh continue their education at 80% which falls into the very high category. The factors are categorized by internal and external factors. Internal factors such as; motivation and goals (0.152), interests (0.201), and external factors such as; parents (0.147), friends (0.156), siblings (0.149), and school environment (0.197). Conclusions: All of these factors can have a positive effect on the interest of Shiva High School to continue to college Keywords: Students’ interest, internal and external Factors, University, quantitative research DOI: http://dx.doi.org/10.23960/jpp.v8.i2.201809